Statistics for Business & Economics, 14th Edition - David R. Anderson; Dennis J. Sweeney; Thomas A. Williams (Cengage Learning, 2019)
Discover how statistical information impacts decisions in today's business world as Anderson/Sweeney/Williams/Camm/Cochran/Fry/Ohlmann's leading STATISTICS FOR BUSINESS AND ECONOMICS, 14E connects concepts from each chapter to real-world practice. This edition delivers sound statistical methodology, a proven problem-scenario approach and meaningful applications that present the latest statistical data and business information with unwavering accuracy. More than 350 new and proven real business examples, a wealth of practical cases and meaningful hands-on exercises highlight statistics in action. You gain practice as exercises and appendices that walk you through using the leading professional statistical software JMP Student Edition 14 and Excel 2016. Trust STATISTICS FOR BUSINESS AND ECONOMICS, 14E as your efficient, powerful solution for mastering business statistics today. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.